Synchronizing estrus in beef heifers with prostaglandin and syncromate B - R.C. DeBenedetti; G.H. Kiracofe; V. Hultine; R.M. McKee; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1976)
Forty-five of 50 heifers were in estrus 1 to 5 days after 7-day synchronization implants were removed. Prostaglandin was injected one day before implants were removed. Thirty-one of the 45 (68.9%) heifers conceived to first artificial insemination service.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Synchronize; Prostaglandin; Syncromate B